2017
DOI: 10.29312/remexca.v7i1.366
|View full text |Cite
|
Sign up to set email alerts
|

Recursos genéticos del algodón en México: conservación ex situ, in situ y su utilización

Abstract: México es el centro de origen del algodón Gossypium hirsutum, 11 de las 13 especies silvestres de Gossypium en el hemisferio occidental son endémicas de nuestro país. Durante el periodo 2009-2011, se realizaron diferentes actividades enfocadas principalmente a la elaboración del diagnóstico de los recursos genéticos del algodón en México. Los resultados obtenidos en este estudio mostraron que en México se han recolectado en las diferentes expediciones realizadas por científicos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…At its indigenous range (i.e., semi-arid tropics and subtropics of the Caribbean, northern South America, and Mesoamerica) (Brubaker and Wendel, 1994), upland cotton exists as a complex of wild-to-domesticated forms that belong to the primary gene pool of the species (Brubaker and Wendel, 1994;Andersson and de Vicente, 2010). Presently, in Mexico-its center of origin, diversity, and domestication (Ulloa et al, 2005;Burgeff et al, 2014;Mendoza et al, 2017)-cotton occurs as a continuum of cultivated and highly improved varieties, genetically modified varieties, traditionally managed landraces, feral, and wild populations. Predominantly, wild cotton populations are found in coastal habitats-as part of littoral vegetation or derived from it (Fryxell, 1979)-in scattered patches that conform to metapopulation dynamics (Hanski, 1998;Freckleton and Watkinson, 2002;Wegier et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At its indigenous range (i.e., semi-arid tropics and subtropics of the Caribbean, northern South America, and Mesoamerica) (Brubaker and Wendel, 1994), upland cotton exists as a complex of wild-to-domesticated forms that belong to the primary gene pool of the species (Brubaker and Wendel, 1994;Andersson and de Vicente, 2010). Presently, in Mexico-its center of origin, diversity, and domestication (Ulloa et al, 2005;Burgeff et al, 2014;Mendoza et al, 2017)-cotton occurs as a continuum of cultivated and highly improved varieties, genetically modified varieties, traditionally managed landraces, feral, and wild populations. Predominantly, wild cotton populations are found in coastal habitats-as part of littoral vegetation or derived from it (Fryxell, 1979)-in scattered patches that conform to metapopulation dynamics (Hanski, 1998;Freckleton and Watkinson, 2002;Wegier et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In Mesoamerica, G. hirsutum exists as a complex of wild to domesticated forms ( Brubaker and Wendel, 1994 ); hence, it is an ideal region to characterize the mating system of this upland cotton complex, identify possible differences, and to integrate this information into regional management plans. In Mexico - its center of origin, diversity and domestication ( Ulloa et al, 2005 ; Burgeff et al, 2014 ; Pérez- Mendoza et al, 2016 ) – the complex includes cultivated and highly improved varieties, genetically modified varieties, traditionally managed landraces, feral, and wild populations. All of them belong to the primary gene pool of the species ( Andersson and de Vicente, 2010 ) and gene flow among them occurs, even over long distances ( Wegier et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Bates (1942), and Maes and Robleto (1988) reported that H. inca feeds on cotton, Gossypium https://doi.org /10.22201/ib.20078706e.2022.93.4030 hirsutum (Malvaceae). Gossypium species are distributed throughout Mexico, with a high concentration of diversity of wild species in the Sierra Madre Occidental, the Sierra Madre del Sur and the Trans-Mexican Volcanic Belt (Pérez- Mendoza et al, 2016), places that coincide with the distribution of H. inca (Fig. 17c), but it has not been found in the Yucatán Peninsula.…”
Section: Discussionmentioning
confidence: 99%